2008
DOI: 10.1007/s00531-008-0360-x
|View full text |Cite
|
Sign up to set email alerts
|

The Léon Domain (French Massif Armoricain): a westward extension of the Mid-German Crystalline Rise? Structural and geochronological insights

Abstract: The Léon Domain in the NW part of the French Massif Armoricain is a stack of synmetamorphic nappes displaced from south to north in ductile conditions. From bottom to top, an orthogneissic basement is overthrusted successively by (1) a Lower Nappe of gneiss including mafic eclogites, (2) an Intermediate Nappe of biotite-garnet-staurolite micaschists with mafic blocks, and (3) an upper nappe made up of Neoproterozoic phyllites covered by unmetamorphosed Paleozoic sedimentary series. This microstructural study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 42 publications
(63 reference statements)
1
42
0
Order By: Relevance
“…Our dating of the St-Renan granite is compatible within error limits with the 321 ± 5 Ma age on monazites previously obtained by the EMPA technique (Faure et al, 2010).…”
Section: In Situ U/pb Geochronologymentioning
confidence: 75%
See 4 more Smart Citations
“…Our dating of the St-Renan granite is compatible within error limits with the 321 ± 5 Ma age on monazites previously obtained by the EMPA technique (Faure et al, 2010).…”
Section: In Situ U/pb Geochronologymentioning
confidence: 75%
“…Available U-Th/Pb dating of monazites yielded ages of 321 ± 5 Ma for the syntectonic emplacement of the St-Renan granite along the NASZ (Faure et al, 2010), and ages of 338 ± 5 Ma (Faure et al, 2010), and 315-305 Ma (Schulz, 2013) for the amphibolite-type metamorphism Paquette and Tiepolo (2007). Detailed analytical procedures and conditions used in this study can be found in Hurai et al (2010Hurai et al ( , 2012.…”
Section: In Situ U/pb Geochronologymentioning
confidence: 97%
See 3 more Smart Citations